The Role of Personal Biological Resource in the Job Demands-Control-Support Model: Evidence From Stress Reactivity - Deng, Huihua; Zhuo, Yuli; Qi, Xingliang; Wu, Hanyao; Liu, Yapeng; Li, Jianmei; Jin, Caixiang (Frontiers in Psychology, 2021)
Job resources can buffer the deleterious effect of adverse work environments. Extant studies on the interaction pattern between job resources and adverse environments were confined to the diathesis stress model. This traditional perspective has received the challenge from the differential susceptibility model and the vantage sensitivity model. Additionally, stress reactivity may be one of important job resources at personal biological level, but its moderating role was short of empirical research. This study aimed to examine how stress reactivity interacts with work environments in predicting job burnouts among 341 Chinese hospital female nurses. This study selected job control and job support representative of supportive environments and psychological demands representative of an adverse environment and the cortisol content in 1-cm hair segment as a biomarker to assess individual’s stress reactivity in one month. The nurses self-reported their work environments and job burnouts and provided 1-cm hair segments closest to the scalp. Hair cortisol content was determined with high performance liquid chromatography-tandem mass spectrometry. The interaction pattern was examined with multiple linear regressions and the analysis of region of significance (RoS). The regression revealed that the interaction of hair cortisol content with job control could positively predict professional efficiency among nurses, and with psychological demands could negatively emotional exhaustion, and with coworker support could negatively professional efficiency. The RoS analysis revealed that nurses with high cortisol level had not only significantly higher professional efficiency than those with low cortisol level in high job control, but also significantly lower professional efficiency in low job control. Nurses with high cortisol level had significantly higher emotional exhaustion than those with low cortisol level in low psychological demands. Nurses with low cortisol level had not only significantly higher professional efficiency than those with high cortisol level in high coworker support, but also significantly lower professional efficiency in low coworker support. The interaction patterns of stress reactivity with both job control and coworker support were consistent with the differential susceptibility model, but the interaction between stress reactivity and psychological demands supported the vantage sensitivity model.